O polskiej historiografii ludobójstwa Ormian. Perspektywa krytyczna w świetle międzynarodowego stanu badań. Część I - Krzysztan, Bartłomiej (Studia polityczne, 2023)
The Armenian Genocide, which took place from 1915 to 1917, is one of the most crucial events defi ning the character of both the fi nal period of the Ottoman Empire and the southern front of World War I. It is also a core identity reference for Armenians and a matter of memory dispute with the Turkish Republic. Since the 1970s, it has been a relevant research space for historians. Surprisingly, in Polish historiography, the subject is only marginally addressed, and its bibliography is puzzlingly limited. The article aims to discuss the Polish historiography of the Armenian Genocide in the broader context of world research. The description of the number of Polish inputs devoted to the Armenian Genocide provides background for the main research problem – a refl ection on the shape of genocide narratives created by Polish historians. This makes it possible to indicate the discursive structures that determine the historical narratives on the Armenian Genocide. Hypothetically, they result from both the time in which they were created and the authors’ axiology and worldview. The article is divided into two parts. The fi rst, in addition to the introduction and description of the state of research, focuses on the interpretation of all Polish historical texts concerning the issue of the Armenian Genocide. A critical analysis is devoted to both compact monographs and broader historical works in which reference is made to the issue of the genocide, above all in the context of the historiography of the declining period of the Ottoman Empire.